2018
DOI: 10.1155/2018/4902941
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibility of Mycobacterium abscessus and Mycobacterium fortuitum Isolates to 30 Antibiotics

Abstract: Objective Nontuberculous mycobacteria (NTM) cause various diseases in humans and animals. Recently, the prevalence of NTM-related disease has been on the rise, becoming an emerging public health problem. The aim of this study was to determine the antibiotic susceptibility profiles of clinical isolates of Mycobacterium abscessus and Mycobacterium fortuitum. Methods. We performed susceptibility tests on 37 clinical NTM isolates to 30 antibiotics with the microdilution method recommended by the Clinical and Labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 40 publications
5
49
1
Order By: Relevance
“…The present study found that 2/3 (66.6%) of M. fortiutum isolates were susceptible to CIP, and all the isolates (3/3) were resistant to the remaining tested drugs. In the recent year, a research study reported from China indicated that all M. fortiutum (17/17) isolates were extremely resistant to RIF, INH, and EMB (28), which is consistent with the results of this study. Other previous studies reported that M. fortuitum isolates were susceptible to CIP and AMK at variable MIC ranges.…”
Section: Patient Characteristics and Clinical Featuressupporting
confidence: 91%
“…The present study found that 2/3 (66.6%) of M. fortiutum isolates were susceptible to CIP, and all the isolates (3/3) were resistant to the remaining tested drugs. In the recent year, a research study reported from China indicated that all M. fortiutum (17/17) isolates were extremely resistant to RIF, INH, and EMB (28), which is consistent with the results of this study. Other previous studies reported that M. fortuitum isolates were susceptible to CIP and AMK at variable MIC ranges.…”
Section: Patient Characteristics and Clinical Featuressupporting
confidence: 91%
“…It was 40.9% in our study, which was in agreement with the rates reported in Beijing 28 and Japan. 24 However, studies conducted in 2017 in Taiwan (61%), 23 2015 in Australia (68%), 29 and 2018 in Shanghai (65%) 30 reported higher rates of IPM resistance. Notably, the M. abscessus isolates in our study had a higher resistance rate to FOX (34.02%) than the M. abscessus strains in a study in Japan (16.7%).…”
Section: Discussionmentioning
confidence: 98%
“…However, they seem to be less active against RGM [11,34,35]. In contrast, bedaquiline exhibited clear inhibitory effects against various species of SGM and RGM, including MFC in different studies [11,12,17,20,33,36]. Bedaquiline has mostly been described as bacteriostatic but bactericidal activity for several MFC-strains has been reported [20,22,36].…”
Section: Discussionmentioning
confidence: 99%
“…Published treatment recommendations and guidelines are mainly based on case studies, clinical experience of experts and antimicrobial susceptibility testing [1,10]. As with all other NTM-species, MFC-isolates do generally not respond to first-line antituberculous drugs and may be naturally or secondarily resistant to several antimicrobial agents [11][12][13]. MFC-susceptibility to amikacin, fluoroquinolones, sulfonamides, imipenem, linezolid, cefoxitin, doxycycline, minocycline, and clarithromycin [1] has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation